Analisis Tarif Angkutan Umum Berdasarkan Biaya Operasi Kendaraan - Muhammad Zardi; Meliyana Meliyana; Defi Mahdiahinda (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The aim of this study is to analyze the Vehicle Operational Cost (VOC) and tariff based on the calculation of VOC and compare with the prevailing tariff in Blang Pidie-Banda Aceh route. Primary data was carried out by surveys, among others, physically survey of the vehicles, number of vehicles and passengers, and investigation survey. Secondary data was obtained from the relevant government institutions. The results of the analysis showed that the average passenger load factor of the inter-city transportation route of Blang Pidie-Banda is 56.25%. The average tariff set by the government is Rp. 106,500/passenger, the average tariff calculated by VOC for Blang Pidie-Banda Aceh route is Rp. 114,014/passenger, while the average rate applied in the field is Rp. 125,000/ passenger. The calculation of Cost of Production (COP) is Rp. 103,649/passenger-km. While the ability to pay (ATP) of the public transport services users is Rp. 208,333. Tariffs based on Vehicle Operating Cost (VOC) are smaller than the prevailing rates in the field and the rates applicable in the field are also higher than the rates set by the local municipality.